The Impact of Personality Traits on Sexual Satisfaction and Frequency of Sex: Does It Differ Between Single and Partnered Individuals? - Uwe Jirjahn; Martha Ottenbacher (Institute of Labor Economics (IZA), 2025)
Using representative data from Germany, this study compares the role of the Big Five personality traits in the sex life of single and partnered individuals. While extraversion has a positive influence on the sex life of both single and partnered individuals, the influence is much stronger for singles. By contrast, the positive role of conscientiousness in sexual fulfillment is stronger for partnered than for single individuals. Openness to experience and agreeableness play a positive role only in the sex life of partnered individuals. Neuroticism has a detrimental impact on people's sex life with the impact being stronger for singles than for partnered individuals. The empirical findings fit our theoretical considerations. Personality traits play different roles in the sex life of single and partnered individuals as the sexual relationships of these individuals are characterized by different time horizons.
Keywords: D91; I31; J10; J12; 330; big five personality traits; casual sex; singlehood; romantic relationship; sexual well-being; frequency of intercourse; family economics